One-pot synthesis, characterization and crystal structure determination of novel 1,4,5-Trisubstituted 1,2,3-Triazole with two conformational isomers: 1-Benzyl-5-((4- methoxyphenyl)ethynyl)-4-phenyl-1H-1,2,3-triazole - Ahmed, M.N.; Yasin, K.A.; Khan, B.A.; Riaz, M.; -, Sadiq-Ur-Rehman; Lo, K.M.; Naseer, M.M.; Arshad, I.; Irshad, M. (Fujian Institute of Research of the Structure of Matter, 2016)
The title compound 1-benzyl-5-((4-methoxyphenyl)ethynyl)-4-phenyl-1H-1,2,3- Triazole (C24H19N3O) was designed and synthesized using one-pot strategy and structural characterization was done by single-crystal X-ray diffraction, NMR, IR and MS. This compound was crystallized out from an ethanolic solution in triclinic system, space group P1 with a = 9.9038(9), b = 10.2928(9), c = 18.8715(19) Å, α = 103.541(6), β = 90.507(7), γ = 97.157(7)°, V = 1854.2(3) Å3, Z = 4, crystal size (mm) = 0.25 × 0.1 × 0.1 and Rint= 0.068. Its asymmetric unit contains two independent molecules. The crystal structure of the title compound is stabilized by intramolecular interactions of types C-H.........N and C-H.........O. Additionally, X-ray analysis reveals obvious C-H.........π, π-π stacking interactions between two adjacent aromatic ring planes.